2013
DOI: 10.1155/2013/498583
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation byTaenia crassicepsand Its Antigens

Abstract: Taenia crassiceps is a cestode parasite of rodents (in its larval stage) and canids (in its adult stage) that can also parasitize immunocompromised humans. We have studied the immune response elicited by this helminth and its antigens in mice and human cells, and have discovered that they have a strong capacity to induce chronic Th2-type responses that are primarily characterized by high levels of Th2 cytokines, low proliferative responses in lymphocytes, an immature and LPS-tolerogenic profile in dendritic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 100 publications
4
37
0
Order By: Relevance
“…However, dysregulated inflammatory responses might be analogically detrimental to the host . Consequently, chronic infections with a persisting antigen challenge often result in significant levels of immune hyporesponsiveness . As reported for the other cestode models, we showed that proliferation and IFN‐γ production in mitogen‐activated splenocytes is significantly suppressed during chronic infection.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, dysregulated inflammatory responses might be analogically detrimental to the host . Consequently, chronic infections with a persisting antigen challenge often result in significant levels of immune hyporesponsiveness . As reported for the other cestode models, we showed that proliferation and IFN‐γ production in mitogen‐activated splenocytes is significantly suppressed during chronic infection.…”
Section: Discussionsupporting
confidence: 76%
“…As reported for the other cestode models, we showed that proliferation and IFN-c production in mitogen-activated splenocytes is significantly suppressed during chronic infection. Intriguingly, the suppression of lymphocyte proliferation by related larval cestodes occurred approximately 2 months after infection (2,33), while in our model, it was detectable already 3 weeks after infection. The observed differences could be due to the high invasive potential of M. vogae as compared to slowly developing above-mentioned cestodes.…”
Section: Discussionmentioning
confidence: 56%
“…Importantly, experiments show that reduced Th1/Th17 immune responses and enhanced Th2, MDSC and AAM populations induced by T. crassiceps are able to downmodulate experimental autoimmune encephalomyelitis , type 1 diabetes and acute‐severe DSS‐induced colitis model , in all cases inducing high levels of IL‐4 and IL‐10 but downregulating TNF‐α.…”
Section: Convergence and Divergence In Immunoregulatory Mechanisms Inmentioning
confidence: 99%
“…The observation that parasite antigens are able to mimic the effects of live parasite has led us to thoroughly investigate whether TcES is able to modify the outcome of autoimmune disease development in murine models of disease, as it happens to be a promising therapeutic alternative to actual anti‐autoimmunity drugs .…”
Section: Convergence and Divergence In Immunoregulatory Mechanisms Inmentioning
confidence: 99%
See 1 more Smart Citation